(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Pyogenic granuloma is an acquired benign vascular proliferation. Clinical features are rapid painless, red polypoid papule or nodule growth on skin or mucus. Both surgical and non-surgical treatments are advised for pyogenic granuloma. Arsha vartma is one among Netraroga explained in Vartmagataroga’s according to Acharya Sushruta Arsha vartma tridoshaja chedana Sadhya vyadhi, is characterized by the eruption of a small, rough, lesion in lid margin which resembles Ervaru beeja (size of the lesion is similar to Cucumber Melos seed) and mild pain. Acharya Vagbhata included few other clinical features like burning sensation, bleeding and cure even after removal. Objective: to see the effect of Tilanala kshara in pyogenic granuloma. Methods: A 32 years old male patient visited our OPD of Shalakya Tantra, SJGAMC, Koppal, with complaints of painless slow growing mass on right upper eyelid near lid margin, occasionally bleeding with trauma since 20 days. Patient was diagnosed as Pyogenic granuloma (Arsha vartma). Patient was treated with 1 sitting of Tilanala Kshara Pratisarana and Jathyadhi ghrita ointment for 7 days. Result: complete resolution of pyogenic granuloma was seen in 7 days Conclusion: Chedana, Bhedana, Lekhana Dahana karma of kshara have effect on pyogenic granuloma and prevent the recurrence.